Self-flame-retardant phosphorus-containing phase change energy storage material microcapsule and preparation process thereof

By using phosphorus-containing compounds to form polymer wall layer materials, the organic phase change energy storage materials are microencapsulated, which solves the problems of flammable, easy leakage and slow heat conduction of existing materials, and realizes self-flammable phosphorus-containing phase transformation The thermal conductivity and flame retardant performance of energy storage material microcapsules are improved.

CN119391379AActive Publication Date: 2025-02-07HENAN ACADEMY OF SCI CHEM RES INST CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411514482.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing organic phase change energy storage materials are flammable, prone to leakage and slow thermal conductivity, which limits their practical application in multiple fields.

Method used

The polymer wall layer material is formed by using phosphorus-containing compounds to microencapsulate the organic phase-change energy storage material to form a self-flame-retardant phosphorus-containing energy storage material microcapsules. This method forms a thermal conductivity network through the synergistic action of nanomagnesium oxide and nanoboronitride, and improves thermal conductivity. It also forms a self-flame-retardant wall material by modifying ammonium polyphosphate and phosphorus-containing diamine monomers to prevent leakage and increase Flame retardant performance.

Benefits of technology

The thermal conductivity and flame retardant performance of the self-flame retardant phosphorus-containing phase-change energy storage material microcapsules have been improved, which prevents material leakage and expands its application range in thermal energy storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391379A_ABST
    Figure CN119391379A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of phase change energy storage materials, in particular to a self-flame-retardant phosphorus-containing phase change energy storage material microcapsule and a preparation process thereof, and the preparation process comprises the following steps: preparation of a composite phase change energy storage material, preparation of a phosphorus-containing wall layer material and preparation of the self-flame-retardant phosphorus-containing phase change energy storage material microcapsule. In the preparation process of the composite phase change energy storage material, the hydroxylated magnesium oxide-boron nitride powder is utilized to modify the paraffin, and under the synergistic effect of nano magnesium oxide and nano boron nitride, the heat conductivity of the composite phase change energy storage material can be improved; modified ammonium polyphosphate and phosphorus-containing diamine monomer components are added into a phosphorus-containing wall layer material, and the prepared phosphorus-containing wall layer material is used as a wall layer material of the self-flame-retardant phosphorus-containing phase change energy storage material microcapsule, so that leakage of the composite phase change energy storage material can be prevented; and the flame retardant property of the wall layer material of the self-flame-retardant phosphorus-containing phase change energy storage material microcapsule is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase change energy storage materials, and more specifically, to a self-flame retardant phosphorus-containing phase change energy storage material microcapsule and a preparation process thereof. Background Art

[0002] In order to save energy and fully improve energy efficiency, phase change energy storage technology that uses materials to absorb or release latent heat during phase change has gradually entered people's field of vision. The so-called organic phase change energy storage material is a type of organic compound that can absorb or release a large amount of heat within a specific temperature range and convert its own state between solid and liquid. This type of material has the potential to be widely studied and applied to thermal energy storage solutions in many fields such as building energy conservation, solar thermal utilization, and thermal management of electronic equipment. Compared with inorganic phase change materials, organic phase change materials usually have lower costs, better biodegradability, design flexibility, and less environmental impact.

[0003] Common organic phase change energy storage materials include fatty acids and their derivatives, waxy substances, polymer phase change materials, etc. However, existing organic phase change energy storage materials generally have problems such as flammability, liquid leakage, and slow thermal conductivity. These problems seriously hinder the practical application of phase change energy storage materials in many fields. At present, the solution to this practical problem is to "fix" the organic phase change energy storage material so that it exhibits the properties of solid-solid phase change materials on a macro scale. This method mainly includes microcapsules, chemical grafting, block copolymerization and physical adsorption methods. Among them, microencapsulated phase change energy storage materials can overcome many limitations of organic phase change energy storage materials. By coating the surface with polymers, the leakage of phase change materials is prevented. In addition, the microcapsules have extremely high specific surface area, which increases the thermal energy storage capacity and greatly broadens the application range of phase change energy storage materials.

[0004] In addition, in recent years, frequent fires have caused great harm to human life and property safety. The fields of construction and textiles have put forward new requirements for the fire resistance level of organic phase change energy storage materials. Therefore, flame-retardant phase change energy storage materials have become the research focus in the current phase change energy storage field. At present, the flame retardant modification of phase change energy storage materials is mainly achieved by physically adding flame retardants. However, physically added flame retardants often have defects such as poor dispersibility in organic phase change energy storage materials and easy reduction of thermal conductivity and physical properties of organic phase change energy storage materials. Summary of the invention

[0005] In view of the shortcomings of organic phase change energy storage materials in the prior art, such as being flammable, easy to leak and having slow thermal conductivity, the present invention provides a self-flame retardant phosphorus-containing phase change energy storage material microcapsule and a preparation process thereof, which utilizes a phosphorus-containing compound to form a polymer wall material, and utilizes the polymer wall material to microencapsulate the organic phase change energy storage material, so that the encapsulated organic phase change energy storage material has a self-flame retardant property, can prevent the leakage of the organic phase change energy storage material, and improve the thermal conductivity of the organic phase change energy storage material.

[0006] A self-flame retardant phosphorus-containing phase change energy storage material microcapsule, characterized by comprising the following steps:

[0007] S1: Preparation of composite phase change energy storage material, immersing nano boron nitride in magnesium nitrate solution, and obtaining magnesium oxide-boron nitride powder through dipping, evaporation concentration, drying, grinding and calcination, and performing hydroxylation modification treatment on the obtained magnesium oxide-boron nitride powder, and mixing the obtained hydroxylated magnesium oxide-boron nitride powder with paraffin to obtain modified paraffin, and mixing the modified paraffin with silicate to obtain composite phase change energy storage material;

[0008] S2: Preparation of phosphorus-containing wall layer material, after heating and activating ammonium polyphosphate, grafting melamine on the surface of ammonium polyphosphate to obtain modified ammonium polyphosphate, and mixing the modified ammonium polyphosphate, phosphorus-containing diamine monomer, melamine, formaldehyde solution and deionized water to obtain the phosphorus-containing wall layer material;

[0009] S3: Preparation of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, deionized water, emulsifier and composite phase change energy storage material are mixed and stirred to obtain an oil-in-water emulsion, and the phosphorus-containing wall layer material is uniformly added dropwise to the oil-in-water emulsion. After heating reaction, the self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained after reduced pressure filtration, filter residue collection, washing and drying.

[0010] Further, S1: preparation of composite phase change energy storage material, specifically comprising the following steps:

[0011] S1.1: immerse the nano-boron nitride in a 30% magnesium nitrate solution, wherein the solid-liquid mass ratio of the nano-boron nitride to the 30% magnesium nitrate solution is (1-6): (30-100), ultrasonically disperse for 10-15 minutes, immerse for 1-3 hours, add the impregnated liquid to a rotary evaporator, evaporate and concentrate at 50-75°C for 10-20 minutes, and then dry at 100-120°C for 4-8 hours. After drying, grind and calcine to obtain magnesium oxide-boron nitride powder;

[0012] S1.2: Add magnesium oxide-boron nitride composite powder to a sodium hydroxide solution with a mass fraction of 20%, wherein the solid-liquid mass ratio of magnesium oxide-boron nitride composite powder to sodium hydroxide with a mass fraction of 20% is (1-5):(50-100), and place under an oil bath at 100-120° C., condense and reflux under magnetic stirring for 15-18 hours, and obtain hydroxylated magnesium oxide-boron nitride powder after cooling, suction filtration and drying;

[0013] S1.3: Add hydroxylated magnesium oxide-boron nitride powder to molten paraffin, wherein the amount of hydroxylated magnesium oxide-boron nitride powder added is 3-10% of the mass of the paraffin, and stir magnetically for 40-60 min at 60-65° C. and a speed of 500-600 r / min to obtain modified paraffin;

[0014] S1.4: Modified paraffin wax and silicate are mixed in a mass ratio of (1-4): (1-2), stirred at 60-65° C., magnetically stirred for 60-90 min, and then ultrasonically shaken for 20-40 min to obtain a phase change material mixture;

[0015] S1.5: Transfer the phase change material mixture to a vacuum pressure sealed glass reactor, draw the vacuum degree to 0.01 MPa and maintain the vacuum for 4 to 6 hours to obtain a composite phase change energy storage material.

[0016] Furthermore, in step S1.1, the calcination operation is carried out under a nitrogen atmosphere, the calcination temperature is 380-410° C., and the calcination time is 3-4 hours.

[0017] Further, step S2: preparation of phosphorus-containing wall layer material specifically comprises the following steps:

[0018] S2.1: heating the ammonium polyphosphate to 200-280° C. for activation for 1-3 hours, and then preparing the activated ammonium polyphosphate into an ammonium polyphosphate dispersed aqueous solution with a mass fraction of 1-3%;

[0019] S2.2: adding melamine to the ammonium polyphosphate dispersion aqueous solution, wherein the amount of melamine is 3-6% of the mass of the activated ammonium polyphosphate, and reacting at 200-240° C. for 1-3 hours to obtain modified ammonium polyphosphate;

[0020] S2.3: Mix modified ammonium polyphosphate, phosphorus-containing diamine monomer, melamine, 37-40% formaldehyde solution and deionized water, wherein the mass ratio of modified ammonium polyphosphate, phosphorus-containing diamine monomer, melamine, formaldehyde solution and deionized water is (0.1-0.4):(0.1-1):(1-2):(1.5-2.5):(1-6) to obtain a mixed solution, and then add triethanolamine until the pH value of the mixed solution is 8-8.5, and stir the reaction at 60-80°C for 1-2 hours to obtain a phosphorus-containing wall layer material.

[0021] Further, the phosphorus-containing diamine monomer is at least one of a phosphorus-containing diamine monomer DAPPO, a phosphorus-containing diamine monomer PCDA, a phosphorus-containing diamine monomer BADPO, and bis[4-(3-aminophenoxy)phenyl]phenylphosphine oxide;

[0022] The structural formula of phosphorus-containing diamine monomer DAPPO is as follows:

[0023]

[0024] The structural formula of phosphorus-containing diamine monomer PCDA is as follows:

[0025]

[0026] The structural formula of phosphorus-containing diamine monomer BADPO is as follows:

[0027]

[0028] The structural formula of bis[4-(3-aminophenoxy)phenyl]phenylphosphine oxide is shown below:

[0029]

[0030] Further, step S3: preparing self-flame retardant phosphorus-containing phase change energy storage material microcapsules, specifically comprising the following steps:

[0031] S3.1: Mix deionized water, composite phase change energy storage material and emulsifier, stir at 60-70°C and 800-1500 r / min for 2-5 hours to obtain an oil-in-water emulsion;

[0032] S3.2: The phosphorus-containing wall layer material is uniformly added dropwise to the water-in-oil emulsion, and reacted at 60-70°C for 2-4 hours. Subsequently, after reduced pressure filtration, filter residue collection, washing and vacuum drying, self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained.

[0033] Furthermore, the mixing mass ratio of deionized water, composite phase change energy storage material and emulsifier is (2-10): (1-3): (0.01-0.08).

[0034] Furthermore, the mixing mass ratio of the phosphorus-containing wall layer material to the oil-in-water emulsion is (0.5-1):(1-6).

[0035] Furthermore, the emulsifier is at least one of sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, Span-20, Span-40, Span-60, Span-80, Tween-20, Tween-40, Tween-60, Tween-80 or TritonX-100.

[0036] A self-flame retardant phosphorus-containing phase change energy storage material microcapsule is prepared by the above-mentioned preparation process of the self-flame retardant phosphorus-containing phase change energy storage material microcapsule.

[0037] The present invention has the following advantages:

[0038] 1. In the present invention, paraffin is modified by using hydroxylated magnesium oxide-boron nitride powder. The hydroxyl functional groups on the surface of the hydroxylated composite powder can increase the interaction between the hydroxylated magnesium oxide-boron nitride powder and the paraffin molecules, and promote the uniform distribution of the hydroxylated magnesium oxide-boron nitride powder in the paraffin. Furthermore, under the synergistic effect of nano-magnesium oxide and nano-boron nitride, the nano-magnesium oxide and nano-boron nitride loaded on the surface of the boron nitride can form an effective heat conduction network in the paraffin matrix, increase the diffusion rate of thermal energy, accelerate the absorption and release process of heat, and thus improve the thermal conductivity of the composite phase change energy storage material. In addition, the high thermal stability of boron nitride and magnesium oxide can provide flame retardant protection for the composite phase change energy storage material and slow down the combustion process.

[0039] 2. In the present invention, ammonium polyphosphate is grafted with melamine so that melamine is grafted on the surface of the ammonium polyphosphate. The obtained modified ammonium polyphosphate can effectively improve its dispersibility in the mixed liquid, thereby promoting the modified ammonium polyphosphate with melamine grafted on the surface to be more evenly and effectively dispersed in the phosphorus-containing wall layer material, which helps to improve the flame retardant properties of the wall material of the self-flame retardant phosphorus-containing phase change energy storage material microcapsule.

[0040] 3. In the present invention, modified ammonium polyphosphate and phosphorus-containing diamine monomers, two inorganic phosphorus-containing compounds and organic phosphorus-containing compounds, are added together to form a phosphorus-containing wall material with self-flame retardant properties. The obtained phosphorus-containing wall material is used as the wall material of self-flame retardant phosphorus-containing phase change energy storage material microcapsules. Microencapsulation and coating of the composite phase change energy storage material can effectively prevent leakage of the composite phase change energy storage material, and play a role in protecting the composite phase change energy storage material from leakage. In addition, the self-flame retardant phosphorus-containing phase change energy storage material microcapsules after microencapsulation have extremely high specific surface area, which can effectively increase the thermal energy storage of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The figure is a flow chart of the preparation process of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules in an embodiment of the present invention.

[0042] Figure 2 This is a graph showing the test results of the physical and chemical properties of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules prepared in the examples and comparative examples of the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] A preparation process of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, such as Figure 1 As shown, the specific steps include:

[0046] S1: Preparation of composite phase change energy storage materials,

[0047] S1.1: Immerse the nano-boron nitride in a 30% magnesium nitrate solution, wherein the solid-liquid mass ratio of the nano-boron nitride to the 30% magnesium nitrate solution is 3:50, and ultrasonically disperse for 15 minutes, and then immerse for 3 hours. Add the impregnated liquid to a rotary evaporator, evaporate and concentrate at 75°C for 20 minutes, and then dry at 120°C for 8 hours. After drying, grind and calcine for 3 hours in a nitrogen atmosphere at 400°C to obtain magnesium oxide-boron nitride powder;

[0048] S1.2: Add magnesium oxide-boron nitride composite powder to a 20% sodium hydroxide solution, wherein the solid-liquid mass ratio of magnesium oxide-boron nitride composite powder to 20% sodium hydroxide is 1:20, and reflux under magnetic stirring for 18 hours in an oil bath at 120°C, and obtain hydroxylated magnesium oxide-boron nitride powder after cooling, suction filtration and drying;

[0049] S1.3: Add hydroxylated magnesium oxide-boron nitride powder to molten paraffin, the amount of hydroxylated magnesium oxide-boron nitride powder added is 8% of the mass of paraffin, at 65°C, magnetic stirring for 60 minutes, the speed is 600r / min, to obtain modified paraffin;

[0050] S1.4: Modified paraffin wax and silicate were mixed in a mass ratio of 2:1, magnetically stirred at 65°C for 90 minutes, and then ultrasonically shaken for 40 minutes to obtain a phase change material mixture;

[0051] S1.5: Transfer the phase change material mixture to a vacuum pressure sealed glass reactor, draw the vacuum degree to 0.01 MPa and maintain the vacuum for 6 hours to obtain a composite phase change energy storage material;

[0052] S2: Preparation of phosphorus-containing wall layer materials,

[0053] S2.1: heating the ammonium polyphosphate to 220° C. for activation for 3 h, and then preparing the activated ammonium polyphosphate into a dispersed aqueous solution of ammonium polyphosphate with a mass fraction of 1%;

[0054] S2.2: Add melamine to the ammonium polyphosphate dispersion aqueous solution, the amount of melamine is 6% of the mass of the activated ammonium polyphosphate, and react at 240° C. for 3 hours to obtain modified ammonium polyphosphate;

[0055] S2.3: Mix modified ammonium polyphosphate, phosphorus-containing diamine monomer DAPPO, melamine, 40% formaldehyde solution and deionized water, wherein the mass ratio of modified ammonium polyphosphate, phosphorus-containing diamine monomer DAPPO, melamine, formaldehyde solution and deionized water is 0.4:0.5:2:2:5 to obtain a mixed solution, then add triethanolamine until the pH value of the mixed solution is 8.5, and stir the reaction at 80°C for 2h to obtain a phosphorus-containing wall layer material;

[0056] S3: Preparation of self-flame retardant phosphorus-containing phase change energy storage material microcapsules,

[0057] S3.1: Mix deionized water, sodium dodecyl sulfate and a composite phase change energy storage material, wherein the mass ratio of deionized water, the composite phase change energy storage material and sodium dodecyl sulfate is 8:3:0.06, and stir at 70°C and a speed of 1500 r / min for 5 hours to obtain an oil-in-water emulsion;

[0058] S3.2: The phosphorus-containing wall layer material is uniformly added dropwise to the oil-in-water emulsion, the mass ratio of the phosphorus-containing wall layer material to the oil-in-water emulsion is 1:5, and the reaction is carried out at 70°C for 4 hours. Subsequently, after reduced pressure filtration, filter residue collection, washing and vacuum drying, self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained.

[0059] Example 2

[0060] A preparation process of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, such as Figure 1 As shown, the specific steps include:

[0061] S1: Preparation of composite phase change energy storage materials,

[0062] S1.1: immerse the nano-boron nitride in a 30% magnesium nitrate solution, wherein the solid-liquid mass ratio of the nano-boron nitride to the 30% magnesium nitrate solution is 3:50, and ultrasonically disperse for 10 minutes, and then immerse for 1 hour. The impregnated liquid is added to a rotary evaporator, evaporated and concentrated at 60°C for 10 minutes, and then dried at 100°C for 4 hours. After drying, the powder is ground and calcined at 380°C in a nitrogen atmosphere for 4 hours to obtain magnesium oxide-boron nitride powder;

[0063] S1.2: Add magnesium oxide-boron nitride composite powder to a 20% sodium hydroxide solution, wherein the solid-liquid mass ratio of magnesium oxide-boron nitride composite powder to 20% sodium hydroxide is 1:20, and place under a 100°C oil bath, condense and reflux for 15 hours with magnetic stirring, and obtain hydroxylated magnesium oxide-boron nitride powder after cooling, suction filtration and drying;

[0064] S1.3: Add hydroxylated magnesium oxide-boron nitride powder to molten paraffin, the amount of hydroxylated magnesium oxide-boron nitride powder added is 8% of the mass of paraffin, at 60°C, magnetic stirring for 40 minutes, the speed is 500r / min, to obtain modified paraffin;

[0065] S1.4: Modified paraffin wax and silicate were mixed in a mass ratio of 2:1, magnetically stirred at 60° C. for 60 min, and then ultrasonically shaken for 20 min to obtain a phase change material mixture;

[0066] S1.5: Transfer the phase change material mixture to a vacuum pressure sealed glass reactor, draw the vacuum degree to 0.01 MPa and maintain the vacuum for 4 hours to obtain a composite phase change energy storage material;

[0067] S2: Preparation of phosphorus-containing wall layer materials,

[0068] S2.1: heating the ammonium polyphosphate to 280° C. for activation for 1 h, and then preparing the activated ammonium polyphosphate into a dispersed aqueous solution of ammonium polyphosphate with a mass fraction of 1%;

[0069] S2.2: adding melamine to the ammonium polyphosphate dispersed aqueous solution, wherein the amount of melamine is 6% of the mass of the activated ammonium polyphosphate, and reacting at 200° C. for 1 h to obtain modified ammonium polyphosphate;

[0070] S2.3: Modified ammonium polyphosphate, phosphorus-containing diamine monomer DAPPO, melamine, 40% formaldehyde solution and deionized water are mixed, and the mass ratio of modified ammonium polyphosphate, phosphorus-containing diamine monomer DAPPO, melamine, formaldehyde solution and deionized water is 0.4:0.5:2:2:5 to obtain a mixed solution, and then triethanolamine is added until the pH value of the mixed solution is 8.5, and the mixture is stirred and reacted at 60°C for 1 hour to obtain a phosphorus-containing wall layer material;

[0071] S3: Preparation of self-flame retardant phosphorus-containing phase change energy storage material microcapsules,

[0072] S3.1: Mix deionized water, sodium dodecyl sulfate and a composite phase change energy storage material, wherein the mass ratio of deionized water, the composite phase change energy storage material and sodium dodecyl sulfate is 8:3:0.06, and stir at 65°C and a speed of 800 r / min for 2 h to obtain an oil-in-water emulsion;

[0073] S3.2: The phosphorus-containing wall layer material is uniformly added dropwise to the oil-in-water emulsion, the mass ratio of the phosphorus-containing wall layer material to the oil-in-water emulsion is 1:5, and the reaction is carried out at 60°C for 2 hours. Subsequently, after reduced pressure filtration, filter residue collection, washing and vacuum drying, self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained.

[0074] Example 3

[0075] A preparation process of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, such as Figure 1 As shown, the specific steps include:

[0076] S1: Preparation of composite phase change energy storage materials,

[0077] S1.1: Immerse the nano-boron nitride in a 30% magnesium nitrate solution, wherein the solid-liquid mass ratio of the nano-boron nitride to the 30% magnesium nitrate solution is 1:30, and ultrasonically disperse for 15 minutes, and then immerse for 3 hours. Add the impregnated liquid to a rotary evaporator, evaporate and concentrate at 75°C for 20 minutes, and then dry at 120°C for 8 hours. After drying, grind and calcine for 3 hours in a nitrogen atmosphere at 400°C to obtain magnesium oxide-boron nitride powder;

[0078] S1.2: Add magnesium oxide-boron nitride composite powder to a 20% sodium hydroxide solution, wherein the solid-liquid mass ratio of magnesium oxide-boron nitride composite powder to 20% sodium hydroxide is 1:50, and place under a 120°C oil bath, condense and reflux under magnetic stirring for 18 hours, and obtain hydroxylated magnesium oxide-boron nitride powder after cooling, suction filtration and drying;

[0079] S1.3: Add hydroxylated magnesium oxide-boron nitride powder to molten paraffin, the amount of hydroxylated magnesium oxide-boron nitride powder added is 3% of the mass of paraffin, at 65°C, magnetic stirring for 60 minutes, the speed is 600r / min, to obtain modified paraffin;

[0080] S1.4: Modified paraffin wax and silicate were mixed in a mass ratio of 1:1, magnetically stirred at 65° C. for 90 min, and then ultrasonically shaken for 40 min to obtain a phase change material mixture;

[0081] S1.5: Transfer the phase change material mixture to a vacuum pressure sealed glass reactor, draw the vacuum degree to 0.01 MPa and maintain the vacuum for 6 hours to obtain a composite phase change energy storage material;

[0082] S2: Preparation of phosphorus-containing wall layer materials,

[0083] S2.1: heating the ammonium polyphosphate to 220° C. for activation for 3 h, and then preparing the activated ammonium polyphosphate into a 3% by mass ammonium polyphosphate dispersed aqueous solution;

[0084] S2.2: Add melamine to the ammonium polyphosphate dispersion aqueous solution, the amount of melamine is 6% of the mass of the activated ammonium polyphosphate, and react at 240° C. for 3 hours to obtain modified ammonium polyphosphate;

[0085] S2.3: Modified ammonium polyphosphate, phosphorus-containing diamine monomer DAPPO, melamine, 40% formaldehyde solution and deionized water are mixed, and the mass ratio of modified ammonium polyphosphate, phosphorus-containing diamine monomer DAPPO, melamine, formaldehyde solution and deionized water is 0.1:0.1:1:1:3 to obtain a mixed solution, and then triethanolamine is added until the pH value of the mixed solution is 8.5, and the mixture is stirred and reacted at 80°C for 2h to obtain a phosphorus-containing wall layer material;

[0086] S3: Preparation of self-flame retardant phosphorus-containing phase change energy storage material microcapsules,

[0087] S3.1: Mix deionized water, sodium dodecyl sulfate and a composite phase change energy storage material, wherein the mass ratio of deionized water, the composite phase change energy storage material and sodium dodecyl sulfate is 5:1:0.01, and stir at 70°C and a speed of 1500 r / min for 5 hours to obtain an oil-in-water emulsion;

[0088] S3.2: The phosphorus-containing wall layer material is uniformly added dropwise to the oil-in-water emulsion, the mass ratio of the phosphorus-containing wall layer material to the oil-in-water emulsion is 1:3, and the reaction is carried out at 70°C for 4 hours. Subsequently, after reduced pressure filtration, filter residue collection, washing and vacuum drying, self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained.

[0089] Comparative Example 1

[0090] Compared with Example 1, the difference of Comparative Example 1 is that step S1.2 is removed, and the hydroxylated magnesium oxide-boron nitride powder in step S1.3 is replaced by the magnesium oxide-boron nitride powder obtained in step S1.1, and the paraffin is modified using the magnesium oxide-boron nitride powder to obtain modified paraffin. The other steps remain unchanged to prepare self-flame retardant phosphorus-containing phase change energy storage material microcapsules, which is recorded as Comparative Example 1.

[0091] Comparative Example 2

[0092] Compared with Example 1, the difference of Comparative Example 2 is that step S1.1 is removed, the magnesium oxide-boron nitride composite powder in step S1.2 is replaced by nano boron nitride to prepare hydroxylated boron nitride powder, the hydroxylated magnesium oxide-boron nitride powder in step S1.3 is replaced by hydroxylated boron nitride powder, and paraffin is modified using hydroxylated boron nitride powder to obtain modified paraffin. The other steps remain unchanged to prepare self-flame retardant phosphorus-containing phase change energy storage material microcapsules, which is recorded as Comparative Example 2.

[0093] Comparative Example 3

[0094] Compared with Example 1, the difference of Comparative Example 3 is that step S1.1 is removed, the magnesium oxide-boron nitride composite powder in step S1.2 is replaced by nano magnesium oxide to prepare hydroxylated magnesium oxide powder, the hydroxylated magnesium oxide-boron nitride powder in step S1.3 is replaced by hydroxylated magnesium oxide powder, and paraffin is modified using hydroxylated magnesium oxide powder to obtain modified paraffin. The other steps remain unchanged to prepare self-flame retardant phosphorus-containing phase change energy storage material microcapsules, which is recorded as Comparative Example 3.

[0095] Comparative Example 4

[0096] Compared with Example 1, the difference of Comparative Example 4 is that the modified ammonium polyphosphate in step S2.3 is removed, and the phosphorus-containing diamine monomer DAPPO, melamine, a formaldehyde solution with a mass fraction of 40% and deionized water are stirred and mixed in a mass ratio of 0.5:2:2:5 to obtain a mixed solution, and then triethanolamine is added until the pH value of the mixed solution is 8.5, and the reaction is stirred at 80°C for 2h to obtain a phosphorus-containing wall layer material. The other steps remain unchanged to prepare self-flame retardant phosphorus-containing phase change energy storage material microcapsules, which is recorded as Comparative Example 4.

[0097] Comparative Example 5

[0098] Compared with Example 1, the difference of Comparative Example 5 is that the phosphorus-containing diamine monomer DAPPO in step S2.3 is removed, and the modified ammonium polyphosphate, melamine, 40% formaldehyde solution and deionized water are mixed in a mass ratio of 0.4:2:2:5 and stirred to obtain a mixed solution. Subsequently, triethanolamine is added until the pH value of the mixed solution is 8.5, and the reaction is stirred at 80°C for 2h to obtain a phosphorus-containing wall layer material. The other steps remain unchanged to prepare self-flame retardant phosphorus-containing phase change energy storage material microcapsules, which is recorded as Comparative Example 5.

[0099] The physical and chemical properties of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules in Examples 1-3 and Comparative Examples 1-5 were tested as follows:

[0100] The phase change enthalpy values ​​of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules in the melting and solidification processes in Examples 1-3 and Comparative Examples 1-5 were tested using a differential scanning calorimeter. The test conditions were as follows: under a nitrogen atmosphere, the temperature test range was -20°C to 120°C, the heating rate was 10°C / min, and the sample weight was about 5 mg; the thermal conductivity of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules in Examples 1-3 and Comparative Examples 1-5 was measured using a thermal conductivity tester; the limiting oxygen index of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules in Examples 1-3 and Comparative Examples 1-5 was measured using an oxygen index tester. The test results are as follows: Figure 2 shown.

[0101] like Figure 2 It can be seen that the self-flame retardant phosphorus-containing phase change energy storage material microcapsules in Examples 1-3, whether in terms of melting enthalpy, solidification enthalpy, thermal conductivity or limiting oxygen index, have test results that are better than those in Comparative Examples 1-5, indicating that the composite phase change energy storage material prepared by using modified paraffin wax, the addition of modified ammonium polyphosphate and phosphorus-containing diamine monomers to the phosphorus-containing wall layer material can improve the flame retardant properties of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules prepared. Compared with the modification of paraffin wax by magnesium oxide-boron nitride powder, hydroxylated boron nitride powder and hydroxylated magnesium oxide powder, the paraffin wax modified by hydroxylated magnesium oxide-boron nitride powder is prepared into a composite phase change energy storage material, and then processed to form a self-flame retardant phosphorus-containing phase change energy storage material microcapsule, and the obtained self-flame retardant phosphorus-containing phase change energy storage material microcapsules have better thermal conductivity and better flame retardant properties. In addition, Examples 1-3 use phosphorus-containing wall materials added with modified ammonium polyphosphate and phosphorus-containing diamine monomers DAPPO to prepare the wall materials of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, and their melting enthalpy and solidification enthalpy values ​​are both maintained above 190 J / g, indicating that the addition of modified ammonium polyphosphate and phosphorus-containing diamine monomers, two inorganic phosphorus-containing compounds and organic phosphorus-containing compounds, in the wall materials of flame-retardant phosphorus-containing phase change energy storage material microcapsules can enable the modified ammonium polyphosphate and phosphorus-containing diamine monomers to work together to increase the thermal energy storage of the self-flame retardant phosphorus-containing phase change energy storage material microcapsules, so that the wall materials of the flame-retardant phosphorus-containing phase change energy storage material microcapsules can have good thermal energy storage capacity.

[0102] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A self-flame retardant phosphorus-containing phase change energy storage material microcapsule, characterized in that: The steps include: S1: Preparation of composite phase change energy storage material, immersing nano boron nitride in magnesium nitrate solution, and obtaining magnesium oxide-boron nitride powder through dipping, evaporation concentration, drying, grinding and calcination, and performing hydroxylation modification treatment on the obtained magnesium oxide-boron nitride powder, and mixing the obtained hydroxylated magnesium oxide-boron nitride powder with paraffin to obtain modified paraffin, and mixing the modified paraffin with silicate to obtain composite phase change energy storage material; S2: Preparation of phosphorus-containing wall layer material, after heating and activating ammonium polyphosphate, grafting melamine on the surface of ammonium polyphosphate to obtain modified ammonium polyphosphate, and mixing the modified ammonium polyphosphate, phosphorus-containing diamine monomer, melamine, formaldehyde solution and deionized water to obtain the phosphorus-containing wall layer material; S3: Preparation of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, deionized water, emulsifier and composite phase change energy storage material are mixed and stirred to obtain an oil-in-water emulsion, and the phosphorus-containing wall layer material is uniformly added dropwise to the oil-in-water emulsion. After heating reaction, the self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained after reduced pressure filtration, filter residue collection, washing and drying.

2. The method for preparing the self-flame retardant phosphorus-containing phase change energy storage material microcapsules according to claim 1, characterized in that: Step S1: Preparation of composite phase change energy storage material, specifically comprising the following steps: S1.1: immerse the nano-boron nitride in a 30% magnesium nitrate solution, wherein the solid-liquid mass ratio of the nano-boron nitride to the 30% magnesium nitrate solution is (1-6): (30-100), ultrasonically disperse for 10-15 minutes, immerse for 1-3 hours, add the impregnated liquid to a rotary evaporator, evaporate and concentrate at 50-75°C for 10-20 minutes, and then dry at 100-120°C for 4-8 hours. After drying, grind and calcine to obtain magnesium oxide-boron nitride powder; S1.2: Add magnesium oxide-boron nitride composite powder to a sodium hydroxide solution with a mass fraction of 20%, wherein the solid-liquid mass ratio of magnesium oxide-boron nitride composite powder to sodium hydroxide with a mass fraction of 20% is (1-5):(50-100), and place under an oil bath at 100-120° C., condense and reflux under magnetic stirring for 15-18 hours, and obtain hydroxylated magnesium oxide-boron nitride powder after cooling, suction filtration and drying; S1.3: Add hydroxylated magnesium oxide-boron nitride powder to molten paraffin, wherein the amount of hydroxylated magnesium oxide-boron nitride powder added is 3-10% of the mass of the paraffin, and stir magnetically for 40-60 min at 60-65° C. and a speed of 500-600 r / min to obtain modified paraffin; S1.4: Modified paraffin wax and silicate are mixed in a mass ratio of (1-4): (1-2), stirred at 60-65° C., magnetically stirred for 60-90 min, and then ultrasonically shaken for 20-40 min to obtain a phase change material mixture; S1.5: Transfer the phase change material mixture to a vacuum pressure sealed glass reactor, draw the vacuum degree to 0.01 MPa and maintain the vacuum for 4 to 6 hours to obtain a composite phase change energy storage material.

3. The preparation process of the self-flame retardant phosphorus-containing phase change energy storage material microcapsule according to claim 2, characterized in that: In step S1.1, the calcination operation is carried out under a nitrogen atmosphere, the calcination temperature is 380-410° C., and the calcination time is 3-4 hours.

4. The preparation process of the self-flame retardant phosphorus-containing phase change energy storage material microcapsule according to claim 3, characterized in that: Step S2: Preparation of phosphorus-containing wall layer material, specifically comprising the following steps: S2.1: heating the ammonium polyphosphate to 200-280° C. for activation for 1-3 hours, and then preparing the activated ammonium polyphosphate into an ammonium polyphosphate dispersed aqueous solution with a mass fraction of 1-3%; S2.2: adding melamine to the ammonium polyphosphate dispersion aqueous solution, wherein the amount of melamine is 3-6% of the mass of the activated ammonium polyphosphate, and reacting at 200-240° C. for 1-3 hours to obtain modified ammonium polyphosphate; S2.3: Mix modified ammonium polyphosphate, phosphorus-containing diamine monomer, melamine, 37-40% formaldehyde solution and deionized water, wherein the mass ratio of modified ammonium polyphosphate, phosphorus-containing diamine monomer, melamine, formaldehyde solution and deionized water is (0.1-0.4):(0.1-1):(1-2):(1.5-2.5):(1-6) to obtain a mixed solution, and then add triethanolamine until the pH value of the mixed solution is 8-8.5, and stir the reaction at 60-80°C for 1-2 hours to obtain a phosphorus-containing wall layer material.

5. The process for preparing the self-flaming retardant phosphorus-containing phase change energy storage material microcapsules according to claim 4, characterized in that: The phosphorus-containing diamine monomer is at least one of a phosphorus-containing diamine monomer DAPPO, a phosphorus-containing diamine monomer PCDA, a phosphorus-containing diamine monomer BADPO, and bis[4-(3-aminophenoxy)phenyl]phenylphosphine oxide.

6. The process for preparing the self-flaming retardant phosphorus-containing phase change energy storage material microcapsules according to claim 4, characterized in that: Step S3: Preparation of self-flame retardant phosphorus-containing phase change energy storage material microcapsules, specifically comprising the following steps: S3.1: Mix deionized water, composite phase change energy storage material and emulsifier, stir at 60-70°C and 800-1500 r / min for 2-5 hours to obtain an oil-in-water emulsion; S3.2: The phosphorus-containing wall layer material is uniformly added dropwise to the water-in-oil emulsion, and reacted at 60-70°C for 2-4 hours. Subsequently, after reduced pressure filtration, filter residue collection, washing and vacuum drying, self-flame retardant phosphorus-containing phase change energy storage material microcapsules are obtained.

7. The process for preparing the self-flaming retardant phosphorus-containing phase change energy storage material microcapsules according to claim 6, characterized in that: The mixing mass ratio of deionized water, composite phase change energy storage material and emulsifier is (2-10): (1-3): (0.01-0.08).

8. The process for preparing the self-flame retardant phosphorus-containing phase change energy storage material microcapsules according to claim 7, characterized in that: The mixing mass ratio of the phosphorus-containing wall layer material to the water-in-oil emulsion is (0.5-1):(1-6).

9. The process for preparing the self-flaming retardant phosphorus-containing phase change energy storage material microcapsules according to claim 8, characterized in that: The emulsifier is at least one of sodium dodecyl sulfonate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, Span-20, Span-40, Span-60, Span-80, Tween-20, Tween-40, Tween-60, Tween-80 or TritonX-100.

10. A self-flame retardant phosphorus-containing phase change energy storage material microcapsule, characterized in that: The microcapsule is prepared by the preparation process of a self-flame retardant phosphorus-containing phase change energy storage material microcapsule according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Halogen-free epoxy resin composition, prepreg containing same, laminated board and printed circuit board

    CN106832764A

  • Anti-flaming phase change microcapsule and preparation method thereof

    CN109225085A

  • Preparation method of POSS (Polyhedral Oligomeric Silsesquioxane) modified melamine resin coated ammonium polyphosphate microcapsule flame retardant

    CN114316370A

  • KR20240028762A